Adsorption of Chromium (VI) onto Metakaolin: Isotherms, Modelling and Optimization - Hamza, Abdulhamid; Alao, Abubakar Mashood; Galadima, Mohammed Sani (Journal of Science and Technology, 2019)
This paper focuses on the application of metakaolin as an adsorbent for the removal of hexavalent chromium (Cr(VI)) from aqueous solution. Metakaolin was prepared and characterized using x-ray fluorescence spectroscopy (XRF), scanning electron microscopy (SEM), specific surface area and pH at point of zero charge analysis. Batch adsorption experiments were designed and conducted with the aid of the statistical central composite design in order to study the effects of pH (2â€“10), initial concentration of Cr(VI) (25â€“100 mg/L) and adsorbent dosage (2â€“10 mg/L). Adsorption of Cr(VI) onto metakaolin was described by a model quadratic equation. Analysis of variance revealed significance of the model quadratic equation. The predicted optimum values of the process variables were:  pH of 2.48, initial Cr(VI) concentration of 32.16 mg/L and adsorbent dosage of 7.08 g/L. The experimental percentage adsorption of Cr(VI) obtained under the predicted optimum conditions (34.43 %.) is very to the predicted value of 37.51 %. The adsorption equilibrium data were analyzed using Langmuir, Freundlich and Dubinin-Radushkevich isotherms. The adsorption equilibrium data is best described by the Freundlich isotherm. The maximum adsorption capacity (qmax) for Cr(VI) adsorption onto metakaolin  is 6.36 mg/g. The results showed that metakaolin is a promising adsorbent for the removal of hexavalent chromium from water.